Variasi Bahasa Tukul Arwana di Acara Bukan Empat Mata Trans 7 Dikaji dari Teori Etnografi Komunikasi Dell Hymes - Sigit Marteja (Institut Agama Islam Negeri Curup, 2019)
Analyzed from Dells Hymmes's ethnographic communication theory. This research uses descriptive qualitative methodology. Consists of eight speech acts: a. arrangement b. participant c. ends d. act e. key f. instrument g. norm h. Genre. Basically, all research data are taken from the program